A simulation framework for zoom-aided coverage path planning with UAV-mounted PTZ cameras - Rios, Natalia Chacon; Mondal, Sabyasachi; Tsourdos, Antonios (MDPI, 2025)
Achieving energy-efficient aerial coverage remains a significant challenge for UAV-based missions, especially over hilly terrain where consistent ground resolution is needed. Traditional solutions use changes in altitude to compensate for elevation changes, which requires a significant amount of energy. This paper presents a new way to plan coverage paths (CPP) that uses real-time zoom control of a pan–tilt–zoom (PTZ) camera to keep the ground sampling distance (GSD)—the distance between two consecutive pixel centers projected onto the ground—constant without changing the UAV’s altitude. The proposed algorithm changes the camera’s focal length based on the height of the terrain. It only changes the altitude when the zoom limits are reached. Simulation results on a variety of terrain profiles show that the zoom-based CPP substantially reduces flight duration and path length compared to traditional altitude-based strategies. The framework can also be used with low-cost camera systems with limited zoom capability, thereby improving operational feasibility. These findings establish a basis for further development and field validation in upcoming research phases.
Keywords: 4605 Data Management and Data Science; 46 Information and Computing Sciences; 40 Engineering; 4602 Artificial Intelligence; Analytical Chemistry; 3103 Ecology; 4008 Electrical engineering; 4009 Electronics, sensors and digital hardware; 4104 Environmental management; 4606 Distributed computing and systems software; coverage path planning; unmanned aerial vehicles; pan–tilt–zoom cameras; ground sampling distance; energy efficiency; zoom compensation; terrain-aware imaging; sensor-based adaptation